(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
Teaching adolescents can be challenging, and cybersecurity education is no different. Teachers need to find ways to engage students in the learning by providing some incentives, such as encouraging a sense of curiosity about something in the world around them. In this paper, we discuss one model of instruction, the 5E Model, that has been effective in helping teachers engage students so they have a desire to learn the material. We also discuss the Project-Based Learning method of teaching in which students learn the necessary information for the project as they work through how to complete it. Students’ incentive to learn is based on the need for the learning to solve the problem and complete the capstone project. We combined these two ideas and integrated them into some of the brief activities as well as the project for the week in our summer camp. We will describe two camp activities and then the capstone project and show how the 5E Model was used as the students developed their projects throughout the week. More in-depth learning about the cybersecurity concepts around which the camp was focused built throughout the week. We hope to give others who work with adolescents in informal learning some ideas to help keep students engrossed in the learning opportunities provided to them.